Van der waals and polar intermolecular contact distances: quantifying supramolecular synthons - Ganguly, Parthasarathy; Desiraju, Gautam R. (Chemistry-an Asian Journal, 2008)
Crystal structures are viewed as being determined by ranges and constraints on interatomic contact distances between neighboring molecules. These distances are considered to arise from environment-dependent atomic sizes, that is, larger sizes for isotropic, van der Waals type contacts and smaller sizes for more-polar, possibly ionic contacts. Although the idea of different, or anisotropic, radii for atoms is not new, we developed a method of obtaining atomic sizes that is based on a theoretical framework. Using different atomic sizes for the same atom in different environments, we were able to rationalize some structural observations and anomalies. For example, benzene with the Pbca structure may be described in terms of two types of C center dot center dot center dot H interactions: a longer contact largely of the van der Waals type, and a shorter, structure-determining type (C delta-center dot center dot center dot H delta+), which we term ``n-polar''. Our approach is illustrated with three examples: 1) the equivalence in crystal packing of fluorobenzene, benzonitrile, pyridine N-oxide, and pyridine/HF 1:1 molecular complex, all of which take the not-so-common tetragonal P4(1)2(1)2 space group and are practically isomorphous; 2) the similarity of the Pa3 acetylene and Pbca benzene crystal structures; and 3) the equivalence between an increase in pressure and an increase in the ``n-polar'' contacts in Pbca benzene; in other words, the equivalence between hydrostatic pressure and chemical pressure. In the context of crystal engineering, we describe a method whereby the topological information conveyed in a supramolecular synthon is recast in a more quantitative manner. A particular synthon, and in turn the crystal structure to which it leads, is viable within small ranges of distances of its constituent atoms, and these distances are determined by chemical factors.
Keywords: atomic radii; benzene crystal; engineering; supramolecular chemistry; van der Waals radii

Long-range synthon aufbau modules (LSAM) in crystal structures: systematic changes in C6H6-nFn (0 <= n <= 6) fluorobenzenes - Ganguly, P.; Desiraju, Gautam R. (Crystengcomm, 2010)
We discuss the assembly of a three-dimensional molecular crystal in terms of short-range supramolecular synthons that spontaneously organize themselves according to Aufbau principles into long-range geometries characteristic of the molecules themselves. For this purpose we have examined the systematic changes in the known crystal structures of a family of fluorobenzenes, C6H6-nFn, where 0 <= n <= 6. Crystal assembly is initiated by forming long-range synthon Aufbau modules (LSAM) that carry the imprint of the synthons. For example, when 1 <= n <= 5 the short-range synthons use H center dot center dot center dot F interactions to form the LSAMs. In the n = 0 and n = 6 compounds, the synthons are H center dot center dot center dot C and F center dot center dot center dot C interactions, respectively. The LSAMs are usually one-dimensional. In this study we show that these 1D LSAMs assemble into 2D quasi-hexagonal close-packed layers. The 3D crystal structure is obtained from the various kinds of close-packing known for these 2D layers. The final stages of this 1D -> 2D -> 3D assembly seem to be more influenced by the packing of LSAMs than by any other factor. In these final stages, there may not be so much influence exerted by the stronger short-range synthons. We discuss the evolution of these fluorobenzene crystal structures in terms of putative LSAMs and the purely geometric relationships between the n and (6 - n) compounds that can thus be expected. Such particle-hole pairs show structural similarities. Our discussion is quantified by the interpretation of intermolecular distances in terms of atomic sizes and with qualitative predictions of magnetic model systems.

Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Chemistry in India: unlocking the potential - Arunan, Elangannan; Brakaspathy, Ramasamy; Desiraju, Gautam R.; Sivaram, Swaminathan (Angewandte Chemie-International Edition, 2013)

Use of the term "crystal engineering" in the regulatory and patent literature of pharmaceutical solid forms. some comments - Desiraju, Gautam R.; Nangia, Ashwini (Crystal Growth & Design, 2016)

Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions